Helminths of the black-headed gull (Chroicocephalus ridibundus) from breeding colonies in north-central Poland - Agata N. Stapf; Izabella Rząd; Katarzyna Królaczyk; Piotr Indykiewicz; Wojciech Gruszka (Scientific Reports, 2024)
Abstract Among parasites of the digestive tract of the black-headed gull (Chroicocephalus ridibundus) in Poland, the best known are species of digenetic trematodes and cestodes. Nematodes of this bird species are not well known. Black-headed gulls, due to their varied diet, migration, life in a flock, and changes of habitat, can become infected with various species of helminths, and like synanthropic birds, they can spread the dispersal stages of parasites across urban and recreational areas. In the present study, an attempt was made to identify the helminth fauna of C. ridibundus from breeding colonies in north-central Poland. The aim of the study was to describe the taxonomic structure of parasites of the digestive tract of the black-headed gull and determine the quantitative parameters of their occurrence. A total of 43 black-headed gulls were examined post-mortem for gastrointestinal helminths, resulting in the identification of four cestodes (Paricterotaenia porosa, Lateriporus clerci, Anomotaenia micracantha, and Wardium fusum), three trematodes (Diplostomum pseudospathaceum, Plagiorchis laricola, and Apophallus muehlingi), and three nematodes (Eucoleus contortus, Cosmocephalus obvelatus, and Porrocaecum ensicaudatum). Lateriporus clerci (in adult form), C. obvelatus and P. ensicaudatum (in larval form) were recorded for the first time in the black-headed gull in Poland.